2004
DOI: 10.1210/en.2003-1338
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Oxyntomodulin Reduces Food Intake and Body Weight Gain in Rats

Abstract: Oxyntomodulin (OXM) is a circulating gut hormone released post prandially from cells of the gastrointestinal mucosa. Given intracerebroventricularly to rats, it inhibits food intake and promotes weight loss. Here we report that peripheral (ip) administration of OXM dose-dependently inhibited both fast-induced and dark-phase food intake without delaying gastric emptying. Peripheral OXM administration also inhibited fasting plasma ghrelin. In addition, there was a significant increase in c-fos immunoreactivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
225
2
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(234 citation statements)
references
References 47 publications
3
225
2
4
Order By: Relevance
“…5 It is a satiety signal, which has been shown to reduce energy intake when administered to rodents and humans. [6][7][8][9] We have recently demonstrated that repeated pre-prandial self-administration of oxyntomodulin results in significant weight loss of 2.370.4 kg (2.470.4% body-weight) in overweight and obese study participants over a 4-week period. 9 One mechanism of this weight loss in humans is a decrease in energy intake; it has been observed that oxyntomodulin significantly suppresses energy intake by 1976% when administered intravenously at a dose of 3.0 pmol/kg min 6 and by 2575 to 3579% when administered subcutaneously at a dose of 400 nmols.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 It is a satiety signal, which has been shown to reduce energy intake when administered to rodents and humans. [6][7][8][9] We have recently demonstrated that repeated pre-prandial self-administration of oxyntomodulin results in significant weight loss of 2.370.4 kg (2.470.4% body-weight) in overweight and obese study participants over a 4-week period. 9 One mechanism of this weight loss in humans is a decrease in energy intake; it has been observed that oxyntomodulin significantly suppresses energy intake by 1976% when administered intravenously at a dose of 3.0 pmol/kg min 6 and by 2575 to 3579% when administered subcutaneously at a dose of 400 nmols.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, rodent studies have suggested that increased energy expenditure, as well as reduced energy intake, is responsible for the decrease in body weight observed after administration of oxyntomodulin. 7,8 Rats, which received twice-daily intraperitoneal injections of oxyntomodulin (50 nmol/kg) for seven days demonstrated lower adiposity and body weight than pair-fed animals, despite identical calorie intake. 8 It has been hypothesised that a positive effect of oxyntomodulin on energy expenditure in rodents may occur as a consequence of a change in the thyroid axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OXM is a satiety signal and administration reduces energy intake in both rodents and humans. [19][20][21] Indeed, pre-prandial subcutaneous administration of OXM to overweight and obese humans over a 4-week period resulted in a significant reduction in body weight of 2.3 kg, compared with 0.5 kg for the placebo arm. 21 In addition, OXM has been found to have a beneficial effect on energy usage, in that it increased activity levels back toward 'normal' in overweight and obese volunteers.…”
Section: Oxyntomodulinmentioning
confidence: 99%
“…(2004) reported that OXM increases c‐FOS in the arcuate nucleus of rats. In chickens, c‐FOS immunoreactivity was significantly decreased in the Leghorn male hepatoma and significantly increased in the nucleus infundibuli hypothalami (equivalent of the mammalian arcuate nucleus) by ICV administration of OXM (Cline et al .…”
Section: Introductionmentioning
confidence: 99%